Concurrent Indicators of Gait Velocity and Variability Are Associated with 25-Year Cognitive Change: A Retrospective Longitudinal Investigation - MacDonald, Stuart W. S.; Hundza, Sandra; Love, Janet A.; DeCarlo, Correne A.; Halliday, Drew W. R.; Brewster, Paul W. H.; Lukyn, Timothy V.; Camicioli, Richard; Dixon, Roger A. (Frontiers in Aging Neuroscience, 2017)
Background/Objectives: Physical function indicators, including gait velocity, stride time, and step length, are linked to neural and cognitive function, morbidity, and mortality. Whereas cross-sectional associations are well documented, far less is known about long-term patterns of cognitive change as related to objective indicators of mobility-related physical function. Methods: Using data from the Victoria Longitudinal Study, a long-term investigation of biological and health aspects of aging and cognition, we examined three aspects of cognition-physical function linkages in 121 older adults. First, we examined a simple marker of physical function (3 m timed-walk) as a predictor of cross-sectional differences and up to 25-year change for four indicators of cognitive function. Second, we tested associations between two markers of gait function derived from the GAITRite system (velocity and stride-time variability) and differences and change in cognition. Finally, we evaluated how increasing cognitive load during GAITRite assessment influenced the associations between gait and cognition. Results: The simple timed-walk measure, commonly used in clinical and research settings, was a minor predictor of change in cognitive function. In contrast, the objectively measured indicator of walking speed significantly moderated long-term cognitive change. Under increasing cognitive load, the moderating influence of velocity on cognitive change increased, with increasing variability in stride time also emerging as a predictor of age-related cognitive decline. Conclusion: These findings (a) underscore the utility of gait as a proxy for biological vitality and for indexing long-term cognitive change, and (b) inform potential mechanisms underlying age-related linkages in physical and cognitive function.